Small‐scale open ocean currents have large effects on wind wave heights. Issue 6 (1st June 2017) - Ardhuin, Fabrice; Gille, Sarah T.; Menemenlis, Dimitris; Rocha, Cesar B.; Rascle, Nicolas; Chapron, Bertrand; Gula, Jonathan; Molemaker, Jeroen
Abstract: Tidal currents and large‐scale oceanic currents are known to modify ocean wave properties, causing extreme sea states that are a hazard to navigation. Recent advances in the understanding and modeling capability of open ocean currents have revealed the ubiquitous presence of eddies, fronts, and filaments at scales 10–100 km. Based on realistic numerical models, we show that these structures can be the main source of variability in significant wave heights at scales less than 200 km, including important variations down to 10 km. Model results are consistent with wave height variations along satellite altimeter tracks, resolved at scales larger than 50 km. The spectrum of significant wave heights is found to be of the order of 70 〈 H s 〉 2 / ( g 2 〈 T m 0, − 1 〉 2 ) times the current spectrum, where 〈 H s 〉 is the spatially averaged significant wave height, 〈 T m 0, − 1 〉 is the energy‐averaged period, and g is the gravity acceleration. This variability induced by currents has been largely overlooked in spite of its relevance for extreme wave heights and remote sensing. Plain Language Summary: We show that the variations in currents at scales 10 to 100 km are the main source of variations in wave heights at the same scales. Our work uses a combination of realistic numerical models for currents and waves and data from the Jason‐3 and SARAL/AltiKa satellites. This finding will be of interest for the investigation of extreme wave heights, remote sensing, and air‐sea interactions. As an immediate application, the present results will help constrain the error budget of the up‐coming satellite missions, in particular the Surface Water and Ocean Topography (SWOT) mission, and decide how the data will have to be processed to arrive at accurate sea level and wave measurements. It will also help in the analysis of wave measurements by the CFOSAT satellite. Key Points: Wave height gradients at scales under 100 km are determined by currents The wave height variance at 10 km scale is proportional to the current spectrum If not corrected for by measuring gradients in wave parameters, SWOT error on sea level probably exceed 20% of total allowed error